Short-external-cavity near-infrared diode lasers for use in molecular spectroscopy - Ventrudo, Francis Brian (My University, 1992)
InGaAsP and AlGaAs near-IR laser diodes with a short external cavity (SXC) were characterized and used as single-mode radiation sources for molecular spectroscopy. A module for extended temperature-tuning of the lasers was tested to evaluate their single-mode frequency tuning range. AlGaAs SXC lasers operating at 0.76 μm tuned up to 400 cm⁻¹ in a single mode, a few wavenumbers at a time, with no gaps in frequency coverage. InGaAsP SXC lasers operating at 1.3-1.55 μm tuned up to 200 cm⁻¹ in a similar fashion. A technique was developed to control the behaviour of the longitudinal modes and enhance laser operation. The technique employed interference fringes in the laser output intensity distribution to produce a discriminating signal used in an electrical feedback loop to maintain the external cavity at the optimum length for single-mode operation. Control theory was used to optimize the operation of this feedback loop. The SXC lasers were used in a high-sensitivity absorption spectrometer. The noise sources of the spectrometer were assessed, and the sensitivity obtained with SXC lasers was compared with that obtained with distributed feedback lasers. Both lasers yielded sensitivities of ≈3x10⁻⁶ in units of equivalent absorbance in an equivalent noise bandwidth of 1.25 Hz. The sensitivity was limited by etalon fringes produced by optical components in the detection path. The SXC laser spectrometer was employed to monitor the relative abundance of H₂O/HDO and ¹²CO₂/¹³CO₂. Changes in the relative abundance as small as 1% could be observed. The crystal-field and impurity splitting of the W₁₋₀(0) transition of solid hydrogen were observed with the spectrometer. Finally, frequency measurements were made of the 3v₂← 0 ro-vibrational band of the H₃⁺ molecular ion.
Keywords: Engineering Physics; Engineering Physics